Analisis Efektifitas Penyusunan Anggaran Kegiatan Rutin Pada Kepolisian Daerah Kalimantan Barat - B51106033, MARETA (Jurnal KIAFE, 2013)
The background of this research is the Government of West Kalimantan Regional Police Department in the preparation of the budget by the Indonesian Government Regulation No. 21 Year 2004 on the preparation of the Work Plan and Budget Ministry State / Institutions where police routine realization Kalimanantan western region in 2008-2009 is not yet effective , it can be seen from the variants that occur between the budget and the realization is too big. In 2008 a variant of Rp. 37,473,815,198, - (22.71%) and in 2009 a variant of Rp.18.037.936.424, - (8.33%). The research problem is the budget is applied to the West Kalimantan Regional Police and the factors that influence it is through questionnaires, factors that become obstacles in the preparation of budgets for financial management and accountability. The research method used is descriptive and quantitative methods and data analysis techniques used are efficient and effective way of measuring, literature study, flowcharts and questionnaires. From the results of the discussion in mind that the budget adopted West Kalimantan Regional Police has referred to the Government Regulation No. 21 of 2004 it can be seen from the results of the questionnaire and budget users in performing their duties as a financial manager is in accordance with the duties and functions of each. Factors to be considered for the realization of the management effectiveness and financial accountability is a business and should be run by the Treasury consistent and full responsibility and making accounting system recommended by Government Regulation No. 21 of 2004 as the basis for the regularity and ease of tracking and accountability of evidence- proof of cash. Training skills for employees of government accounting rule that handles accounting and treasurer to provide flexibility in operating the Financial Management and Accountability of government regulatory policy on the Government Accounting Standards.